An Assessment of Trade Policy in Nepal - Regmi, Udaya Raj (Administration and Management Review, 2011)
This paper aims at assessing trade policy 1992 in terms of its contribution to economic growth, foreign direct investment, export diversification; SAARC regional trading arrangements; trade volume; terms of trade, and industrialization of the country, using the various econometric and trade policy related indices. Trade policy has not significantly contributed to growth of the country due to low inflow of foreign direct investment, declining terms of trade, small trade volume, low level of trade diversification in terms of both country and commodity, and small intra-SAARC trade. Despite the liberalization efforts of the government, trade policy has been ineffective in intensifying and diversifying the trade sector and developing the country. Key words: Trade policy; Economic; Nepal Administration and Management Review Volume 22, No. 1, January, 2010 Page: 28-59 Uploaded Date: 2 December, 2011